2007
DOI: 10.1021/bi7001482
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of Tryptophan 372 in Succinyl-CoA:3-Ketoacid CoA Transferase during Aging in Rat Heart Mitochondria

Abstract: The main objective of this study was to test the hypothesis that in vivo post-translational modifications in proteins, induced by the endogenously generated reactive oxygen and nitrogen molecules, can alter protein function and thereby have an effect on metabolic pathways during the aging process. Succinyl-CoA:3-ketoacid coenzyme A transferase (SCOT), the mitochondrial enzyme involved in the breakdown of ketone bodies in the extrahepatic tissues, was identified in rat heart to undergo age-associated increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 62 publications
5
73
3
Order By: Relevance
“…A similar phenomenon was also observed in the alloxan-induced mouse model of diabetes (26). The role of nitration in decreased SCOT activity in humans was confirmed by Rebrin et al (21). By investigating the posttranslational modifications that occurred in proteins during the aging process, tryptophan was identified as a specific in vivo target of nitration and shown to increase SCOT activity.…”
supporting
confidence: 56%
“…A similar phenomenon was also observed in the alloxan-induced mouse model of diabetes (26). The role of nitration in decreased SCOT activity in humans was confirmed by Rebrin et al (21). By investigating the posttranslational modifications that occurred in proteins during the aging process, tryptophan was identified as a specific in vivo target of nitration and shown to increase SCOT activity.…”
supporting
confidence: 56%
“…ONOO − has been shown to be highly reactive with a wide variety of molecules, including deoxyribose, cellular lipids, and protein sulfhydryl moieties, causing direct oxidative tissue damage. Several animal experiments tested the effects of aging upon in vivo RNS formation and demonstrated that aging resulted in increased nitration (Rebrin et al 2007;Zhang et al 2007). Currently, with the clinical trial, we did not find any significant difference in NOx and ONOO − formation between the adult and elderly populations.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effects of RNS are further exacerbated with increased ambient ROS. However, nearly all studies concerning aging, myocardial ischemia/reperfusion (MI/R) injury, ROS, and RNS exacerbating MI/R injury (Rebrin et al 2007;Zhang et al 2007) utilize animal experiments. Aging-related effects with clinical applicability to humans are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although immunoprecipitation can be used for effective enrichment of 3-NT-containing proteins, it is notable that a significant number of nonnitrated proteins coimmunoprecipitate. This apparent lack of specificity may arise from undesired interactions of anti-3-NT antibodies with 3-NT-free proteins (Aulak et al, 2004), such as those which contain 5-hydroxynitrotryptophan (Rebrin et al, 2007), and the predicted pull down of proteins that associate with 3-NT-containing proteins.…”
Section: Beyond Quantification: Specification Of 3-nt Sites In Proteinsmentioning
confidence: 99%